2018
DOI: 10.1038/s41598-018-29468-6
|View full text |Cite
|
Sign up to set email alerts
|

MDM4 contributes to the increased risk of glioma susceptibility in Han Chinese population

Abstract: Recently, MDM4 gene has been reported to be a susceptibility gene for glioma in Europeans, but the molecular mechanism of glioma pathogenesis remains unknown. The aim of this study was to investigate whether common variants of MDM4 contribute to the risk of glioma in Han Chinese individuals. A total of 24 single-nucleotide polymorphisms (SNPs) of the MDM4 gene were assessed in a dataset of 562 glioma patients (non-glioblastoma) and 1,192 cancer-free controls. The SNP rs4252707 was found to be strongly associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Nesse ínterim, foram identificados 104 genes comuns relacionados à sobrevivência de pacientes com gliomas, sendo a maioria desses genes envolvidos em vias de sinalização relacionadas com células que afetam a proliferação celular, apoptose e angiogênese (HSU et al, 2019). Além disso, foi detectado um polimorfismo de nucleotídeo único (SNP), principalmente o SNP rs4252707, que está intrínsecamente relacionado com o gene MDM4, o que demonstra um intenso desequilíbrio de ligação com o rs12031912 e rs12028476, que apesar de poucos estudos, limitados em populações europeias, podem sugerir uma interação com a patogênese do glioblastoma (SUN et al, 2018).…”
Section: Resultsunclassified
“…Nesse ínterim, foram identificados 104 genes comuns relacionados à sobrevivência de pacientes com gliomas, sendo a maioria desses genes envolvidos em vias de sinalização relacionadas com células que afetam a proliferação celular, apoptose e angiogênese (HSU et al, 2019). Além disso, foi detectado um polimorfismo de nucleotídeo único (SNP), principalmente o SNP rs4252707, que está intrínsecamente relacionado com o gene MDM4, o que demonstra um intenso desequilíbrio de ligação com o rs12031912 e rs12028476, que apesar de poucos estudos, limitados em populações europeias, podem sugerir uma interação com a patogênese do glioblastoma (SUN et al, 2018).…”
Section: Resultsunclassified
“…[22][23][24] Furthermore, MDM4 has been shown to increase the hazard of GM susceptivity in the Han Chinese population. 25 Additionally, the study by Xie et al identified let-7 to bind MDM4 and contribute to the DNA damage response in GM. 26 Thus, these reports together with our analysis implicate MDM4, and its regulators and targets to be involved in tumor formation and progression in GM.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, the presence of SNP34091 alone does not correlate with cancer risk (Pedram et al 2016); however, in combination with the miRNA expression profile, it predicts tumor size and lymph node infiltration (Anwar et al 2017). Other SNPs in MDMX are associated with an increased risk of glioma (rs4252707) (Sun et al 2018), prostate, and gastric cancer (rs1380576) (Sun et al 2010;Wang et al 2017b) and Parkinson's disease (rs16854023) (Cha et al 2020).…”
Section: Mdm2 and Mdmx Upstream: Regulation Occurs At Every Levelmentioning
confidence: 99%